Men Challenge: Syibhul ‘Iddah Policy for Men in Feminist Legal Theory - Falah, Nabilah (Qanun: Jurnal Hukum Keluarga Islam, 2024)
Feminist legal theory is the view of feminists in criticizing regulations relating to women. There is a 'iddah period policy for husbands issued by the Ministry of Religion through the Director General of Islamic Community Guidance regarding the prohibition of marriage during the wife's 'iddah period, known as syibhul 'iddah which is interesting to research, so the aim of this research is to explain the syibhul 'iddah policy for men through the lens of feminist legal theory. This research is normative research with a statutory and regulatory approach to analyze deductively through feminist legal theory. Based on the research results, it shows that the rules for the 'iddah period for husbands are a form of legal equality which has an impact on men and women who are divorced, so that the 'iddah period becomes a waiting period which also applies to men so that they are careful in terminating the marriage and remarry. The syibhul iddah rules bring updates to the waiting period policy that is gender equitable so that this research contributes to disseminating the iddah policy which also applies to men.